Evolution of the magnetic structure with chemical composition in spinel iron oxide nanoparticles. Issue 32 (23rd July 2015) - Muscas, G.; Yaacoub, N.; Concas, G.; Sayed, F.; Sayed Hassan, R.; Greneche, J. M.; Cannas, C.; Musinu, A.; Foglietti, V.; Casciardi, S.; Sangregorio, C.; Peddis, D.
Abstract : Magnetic properties of iron oxide nanoparticles with spinel structure are strictly related to a complex interplay between cationic distribution and the presence of a non-collinear spin structure (spin canting ). Abstract : Magnetic properties of iron oxide nanoparticles with spinel structure are strictly related to a complex interplay between cationic distribution and the presence of a non-collinear spin structure (spin canting). With the aim to gain better insight into the effect of the magnetic structure on magnetic properties, in this paper we investigated a family of small crystalline ferrite nanoparticles of the formula Co x Ni1− x Fe2 O4 (0 ≤ x ≤ 1) having equal size (≈4.5 nm) and spherical-like shape. The field dependence of magnetization at low temperatures indicated a clear increase of magnetocrystalline anisotropy and saturation magnetization (higher than the bulk value for CoFe2 O4 : ∼130 A m 2 kg −1 ) with the increase of cobalt content. The magnetic structure of nanoparticles has been investigated by Mössbauer spectroscopy under an intense magnetic field (8 T) at a low temperature (10 K). The magnetic properties have been explained in terms of an evolution of the magnetic structure with the increase of cobalt content. In addition a direct correlation between cationic distribution and spin canting has been proposed, explaining the presence of a noncollinear spin structure in terms of superexchange interaction energy produced by the average cationic distribution and vacancies in the spinel structure.